Animal hats : frog hats, elephant hats, cat hats, and more : 15 patterns to knit and show off - Mooncie, Vanessa (Taunton Press, 2012)
Gather knitting know-how for making animal hats of all shapes and sizes. The book features detailed knitting patterns, schematics, and basic animal hat-making techniques--plus how-to instruction for adding a fleecy hat-lining for extra coziness. There are patterns for every animal-lover. Animals included are cat, dog, chicken, rabbit, pig, frog, penguin, cow, elephant, fox, koala, monkey, panda, lion, and mouse. Patterns offer both child and adult sizes, so family members can each have their own hat.